The Effect of Organizational Climate and Self-Efficacy on Organizational Citizenship Behavior (OCB) with Job Satisfaction as an Intervening Variable for Bappeda Employees in Payakumbuh City - Hanifeliza, Rury; Putri, Eka Risma (Jurnal Manajemen Stratejik dan Simulasi Bisnis, 2024)
Abstract This study aims to analyze and examine the effect of organizational climate, self-efficacy on Organizational Citizenship Behavior (OCB) with job satisfaction as an intervening variable in Bappeda employees in Payakumbuh City. This type of research is quantitative with a sample of 37 Bappeda employees in Payakumbuh City. The sampling method uses saturated sampling where all population members are used as samples. This study combines primary and secondary data. Primary data was collected through questionnaires distributed to all employees of Bappeda Payakumbuh City. Secondary data comes from pre-existing sources, such as government documents, archives, and the like. The data were processed using Structural Equation Modeling (SEM) analysis with the SmartPLS application. The results of this study are organizational climate and self-efficacy have a negative but insignificant effect on OCB, job satisfaction has a positive and significant effect on OCB. Other results show that organizational climate and self-efficacy have a positive and significant effect on job satisfaction. This study also proves that organizational climate has a positive and significant effect on OCB through job satisfaction, as well as self-efficacy also has a positive and significant effect with job satisfaction as an intervening variable. Abstrak Penelitian ini bertujuan untuk menganalisis dan menguji pengaruh iklim organisasi, efikasi diri terhadap Organizational Citizenship Behavior (OCB) dengan kepuasan kerja sebagai variabel intervening pada pegawai Bappeda Kota Payakumbuh. Jenis penelitian adalah kuantitatif dengan sampel Pegawai Bappeda Kota Payakumbuh yang berjumlah 37 orang. Metode Pengambilan sampel menggunakan sampling jenuh dimana semua anggota populasi digunakan sebagai sampel. Penelitian ini menggabungkan data primer dan sekunder. Data primer dikumpulkan melalui kuesioner yang disebarkan kepada seluruh pegawai Bappeda Kota Payakumbuh. Data sekunder berasal dari sumber yang sudah ada sebelumnya, seperti dokumen pemerintah, arsip, dan sejenisnya. Data diolah menggunakan analisis Structural Equation Modeling (SEM) dengan aplikasi SmartPLS. Hasil dari penelitian ini adalah iklim organisasi dan efikasi diri berpengaruh negatif tapi tidak signifikan terhadap OCB, kepuasan kerja berpengaruh positif dan signifikan terhadap OCB. Hasil lain menunjukkan bahwa iklim organisasi dan efikasi diri berpengaruh positif dan signifikan terhap kepuasan kerja. Penelitian ini juga membuktikan bahwa iklim organisasi berpengaruh positif dan signifikan terhadap OCB melalui kepuasan kerja, demikian juga efikasi diri juga berpengaruh secara positif dan signifikan dengan kepuasan kerja sebagai variabel intervening. Kata kunci : OCB, Iklim organisasi, Efikasi diri, kepuasan kerja, SEM PLS